Uses of Artificial Intelligence in Teaching Children with Special Needs - Khairi, dr. Samah Thaer Khairi (Sulaimani Journal for Humanities, 2026)
In recent years, the world has witnessed a revolution in the field of artificial intelligence, the effects of which have appeared in most areas of life, whether in medicine, engineering, armament, manufacturing, investment, space sciences, communications, and others, which places a great serious responsibility on the ministries designated for education to develop their policies, curricula, and strategies to keep pace with the data of the modern artificial revolution, which was the spark that lit up new spaces for educators in the search for enriching the culture of artificial intelligence and integrating it theoretically and practically in the various stages of education. Given the importance of the education sector in the development process, especially with regard to providing the needs of the labor market for people with different specializations and skills that are closely linked to development policies and programs, the education sector is the source of all new technologies that are being introduced, and here comes artificial intelligence. There is no room for any development in education unless its members are aware of the various implications of these technologies, and know their types and root them to keep pace with their development and determine ways to adopt and invest them in educational work in a way that enables it to face the challenges of the future. The educational process is not isolated from these developments and influences in its various aspects and categories of knowledge and humanity; Among the groups that can greatly benefit from artificial intelligence are children with special needs, whose education requires special support to meet their educational needs, which are diverse and deep in terms of perception and skills.
Keywords: Artificial Intelligence; Teaching Children; People with Special Needs